Deceased Donor Kidney Transplantation in the Eurotransplant Senior Program (ESP): A Single-Center Experience from 2008 to 2013 - Jacobi, Johannes; Beckmann, Sophie; Heller, Katharina; Hilgers, Karl Friedrich; Apel, Hendrik; Spriewald, Bernd; Eckardt, Kai-Uwe; Amann, Kerstin Ute (Annals of Transplantation, 2016)
BACKGROUND The aim of this study was to evaluate the outcome after transplantation of deceased allografts in donor/recipient pairs aged >=65 years enrolled in the Eurotransplant Senior Program (ESP). MATERIAL AND METHODS In this retrospective cohort study we evaluated data from 89 patients transplanted under the ESP protocol from 2008 to 2013. Outcome parameters included graft and patient survival, rate of biopsy-proven acute rejections (BPAR), peri- and post-operative complications, tumor development, development of donor-specific antibodies (DSA), and the prognostic role of preimplantation biopsies. RESULTS One-year patient and allograft survival rates were 92.1% and 84.3%, respectively. During follow-up, 23 (26%) patients died; the major cause of death was sepsis, followed by cardiovascular events and malignancies. BPAR episodes were frequent within the first year ( 33%) and overall were less common in patients treated with tacrolimus. Post-transplant malignancies were seen in 15 (17%) patients. During follow-up, 16 (18%) patients developed DSA; patients with delayed graft function (DGF) were more likely to develop DSA (p=0.029). A higher preimplantation biopsy score was associated with DGF but did not predict later graft outcome. CONCLUSIONS The results highlight increased risks in ESP transplant candidates and the importance of careful surveillance of this patient group.
EVALuna2:3834